Study of Vegetation and Perception Characteristic of Coastal Community in Utilizing Mangrove in Labuan Uki Bay, Bolaang Mongondow Regency - Moh. Ikhsan Z. Runtukahu; Ridwan Lasabuda; Adnan S. Wantasen (Jurnal Ilmiah PLATAX, 2017)
Bay of Labuan Uki located in Lolak district, Bolaang Mongondow regency, North Sulawesi province has the potential of coastal area and sea, especially mangrove ecosystem to be used and preserved for the public welfare.Based on that, the purpose of the research is  to (1) analyze the community structure and mangroves forest area at the Bay of Labuan Uki (2) analyze the perception Bay of Labuan Uki coastal area societies in the utilization of mangrove ecosystems. The results of this research found that 5 families mangrove Avicenniaceae, Rhizophoraceae, Sonneratiaceae, Arecaceae and Myrsinaceae and 14 species, mangrove area is now 125.49 Ha with the conditions of thickness and density of mangrove largely been sparse due to logging for over functioned. The public perception most desire sustainable use, so need for rehabilitation, socialization to raise public awareness, economic alternatives for utilizing mangrove either directly or indirectly, and making of regulations related to the mangrove forests such as the Village Regulations together (Sauk, Baturapa II, Labuan Uki) and or the Local Regulation of Bolaang Mongondow Regency to maintain and preserve the mangrove forests at the Bay of Labuan Uki today.Keywords: Mangrove, Public Perception, Bay of Labuan Uki. AbstrakTeluk Labuan Uki terletak di Kecamatan Lolak, Kabupaten Bolaang Mongondow, Provinsi Sulawesi Utara memiliki potensi wilayah pesisir dan laut terutama ekosistem mangrove untuk dimanfaatkan dan dilestarikan demi kesejahteraan masyarakat. Berdasarkan hal tersebut, penelitian ini bertujuan untuk (1) Menganalisis struktur komunitas dan luasan hutan mangrove di kawasan Teluk Labuan Uki (2) Menganalisis persepsi masyarakat pesisir Teluk Labuan Uki dalam pemanfaatan ekosistem mangrove. Hasil penelitian ini menemukan 5 famili mangrove yaitu Avicenniaceae, Rhizophoraceae, Sonneratiaceae, Arecaceae dan Myrsinaceae dan 14 spesies, luasan mangrove saat ini 125,49 Ha dengan  kondisi ketebalan serta kerapatan mangrove  sebagian besar sudah jarang akibat penebangan untuk dialihfungsikan. Persepsi masyarakat sebagian besar menginginkan pemanfaatan yang berkelanjutan, maka perlu adanya rehabilitasi, sosialisai untuk membangkitkan kesadaran masyarakat, alternatif ekonomi bagi yang memanfaatkan mangrove baik secara langsung maupun tidak dan pembuatan regulasi terkait hutan mangrove berupa Peraturan Desa bersama (Sauk, Baturapa II, Labuan Uki) dan atau Peraturan Daerah Kabupaten Bolaang Mongondow untuk menjaga dan melestarikan hutan mangrove di Teluk Labuan Uki saat ini.Kata kunci : Mangrove, Persepsi Masyarakat, Teluk Labuan Uki.